2023
DOI: 10.3390/su151310464
|View full text |Cite
|
Sign up to set email alerts
|

Study on Urban Expansion and Population Density Changes Based on the Inverse S-Shaped Function

Abstract: For decades, the continuous advance of urbanization has led to the continuous expansion of urban land and rapid increase in the total area of cities. The phenomenon of urban land expansion faster than population growth has become widespread. High population density can lead to problems such as traffic congestion and exacerbated air pollution and can hinder sustainable development, affecting the quality of life of urban residents. China is currently in a phase of rapid urbanization, with high urban population d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Urban sustainability demands a better future in an urban environment [26]. The world is becoming intelligent and efficient in every sphere of life, which demands a high level of living in every corner of a region [27]. Therefore, a healthy environment, pure air without any pollution, and land with all ecosystem services are needed for a sustainable city [28].…”
Section: Review Of Literaturementioning
confidence: 99%
“…Urban sustainability demands a better future in an urban environment [26]. The world is becoming intelligent and efficient in every sphere of life, which demands a high level of living in every corner of a region [27]. Therefore, a healthy environment, pure air without any pollution, and land with all ecosystem services are needed for a sustainable city [28].…”
Section: Review Of Literaturementioning
confidence: 99%
“…It also affects the degree of social cohesion associated with a given population. Areas with high population density may experience elevated social tension due to the presence of more people nearby (Lu et al, 2023).…”
Section: Social Condition Of Cipanas City Candidate Areamentioning
confidence: 99%
“…From the perspective of the spatial pattern of O 3 pollution, the most serious O 3 pollution area is in the border area of Hebei, Shandong, and Henan Provinces, that is, the southern part of Hebei, the northern part of Henan, and the western part of Shandong. This is due to the dense population of these areas [15,49,50], the high level of human activities [51,52], and the resulting high anthropogenic emissions, while the strong ultraviolet radiation and high temperature in summer [46][47][48] greatly enhances the photochemical reaction level of O 3 , and the ozone pollution level is also the most serious. Furthermore, it was observed that the concentrations of O 3 pollution were comparatively reduced during the spring season when analyzed against those prevalent in the summer period.…”
Section: Spatiotemporal Distribution Of the Estimated Mda8 In The Ncpmentioning
confidence: 99%